PENGARUH FAKTOR FUNDAMENTAL DAN TEKNIKAL TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ikromah Ikromah; Muhammad Yusuf (ITB AAS INDONESIA, 2024)
This study aimed to obtain empirical evidence about the influence of fundamental factor and technical factor on stock returns. The population in this study is companies list in Indonesia Stock Exchange 2015-2017. The study sample was determined by purposive sampling method so that obtained as 192 samples. The data analysis technique used is multiple linier regression. The results of this study showed that the profitability, cash flow operating activities, dan risk (beta) have positive significance effect on stock returns, whereas exchange rate and interest rate have negative significance effect on stock returns. Meanwhile, leverage and Economic Value Added (EVA) haven’t significance effect on stock returns. Keywords : stock returns, profitability, cash flow operating activities, exchange rate, beta